A World Trading System for the Twenty-First Century - Beshkar, Mostafa (Journal of Economic Literature, 2023)
Mostafa Beshkar of Indiana University-Bloomington reviews “A World Trading System for the Twenty-First Century” by Robert W. Staiger. The Econlit abstract of this book begins: “Discusses the success of the General Agreement on Tariffs and Trade (GATT) and its ideal economic environment, evaluating whether twenty-first-century changes in the global economy imply the need for changes in the design of the World Trade Organization (WTO) system.”